Traumatic brain injuries in a paediatric neurosurgical unit: A Queensland experience. (December 2019) - Stephens, Sean; Campbell, Robert; Chaseling, Raymond; Ma, Norman
Highlights: Traumatic brain injury is prevalent among children with broad injury spectrum. Available data on children requiring neurosurgical admission post-injury is sparse. Falls and traffic accidents were found to be the most common injury mechanisms. Considerable over-triage was identified among those admitted. Abstract: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in children with a broad injury spectrum and associated continuum in the level of care required. A dearth of data exists regarding children requiring inpatient neurosurgical admission following TBI. A retrospective study of children 0–16 years-old admitted to the neurosurgical unit of a level-1 paediatric trauma hospital in Queensland, Australia following TBI was conducted focusing on the demographics, clinical characteristics, and management of these patients to guide those involved in their management, and identify areas for improvement in injury prevention and trauma system management. Over 48 months, 671 patients were identified (62.6% male) with median age 5.0 years, the majority transferred from peripheral centres. Falls (47.2%) and traffic accidents (21.5%) were the most common mechanisms. Non-displaced skull fracture was the most common injury. Moderate or severe TBI (GCS 3–12) was seen in 14.8% of whom were more likely to require surgery, intensive care, or suffer polytrauma. Clinically significant TBI, defined as moderate/severe TBI, polytrauma, death, requiring neurosurgery, intensive care admission, intubation, or admission three or more nights was detected in 57.97% with higher rates in transferred patients (62.9%) versus primary presentations (50.6%). Mechanisms involving low kinetic forces especially low-height falls and children with non-surgical pathology were less likely to meet criteria for clinically significant TBI. Opportunity exists to optimise triage and transfer practices within the trauma network to minimise the economic and social implications of over-triage with many children requiring only brief observation.